KAJIAN POTENSI SAGU SEBAGAI SUMBER PANGAN LOKAL DI NEGERI TUHAHA KECAMATAN SAPARUA TIMUR KABUPATEN MALUKU TENGAH - M. Luhukay; R. G. Risamasu; R. Tomasoa (Agrinimal Jurnal Ilmu Ternak dan Tanaman, 2019)
Food was a fundamental necessity for human survival and at the same time for the integrity of a nation so that its existence must be available at all times and its fulfillment must be fulfilled. For rural people in Maluku, food security depends largely on local foodstuffs such as sago, tubers, bananas, corn, breadfruit and others. Local food resources available in most region in Maluku in particular sago, if managed properly can supportstrengthen the needs of household and local food reserves and in turn reduce dependency on rice. This research aims to identify the potential of sago as well as determine the patterns and levels of public consumption against sago as local food. The research was conducted in East Saparua district land Tuhaha with survey methods and structured interviews. The results of the research found 167 haof sago plantation available in Tuhaha. At least 24 tree/Ha mature sago tree stands (MT) which produced484kgs raw starch per tree or 1122 tons dried sago starch. The percentage of local food consumption respectively was 15%sago, 27% combination of sago, tubers and banana, 32%combination of sago, tubers, banana and rice amounted, and 26% purely rice.